Utilizing Social Media as a Means of Education on Danger Signs of Pregnancy for the Community - Helena Febbri Saraswati; Ditya Fajar Rizkizha (Journal of Interdisciplinary Social Sciences and Humanities, 2025)
This study examines the internship experiences of Visual Communication Design students in the Merdeka Belajar Kampus Merdeka (MBKM) program at RS Dr. OEN SOLO BARU, focusing on the use of social media for health education. Conducted from March 18 to June 30, 2025, the internship involved various visual design projects, including a public awareness campaign on recognizing pregnancy danger signs. The primary objective was to improve public understanding of pregnancy complications as a preventive measure against maternal and neonatal health risks. A descriptive qualitative approach was applied, with data gathered through consultations with general practitioners and a review of relevant health literature. The findings reveal that the public generally recognizes heavy bleeding and prolonged labor as danger signs but demonstrates limited awareness of other critical symptoms such as blurred vision, persistent headaches, and swelling. This gap in knowledge poses a significant risk for delayed medical intervention and increased complications. The internship activities showcased the potential of combining evidence- based health information with visually engaging social media content to reach broader audiences. The study concludes that integrating accurate medical knowledge into creative visual communication can effectively strengthen public awareness and prompt timely health-seeking behavior. These results highlight the importance of collaboration between healthcare professionals and visual communication practitioners in developing impactful health education initiatives.